Levels of addition of green defect on the chemical composition of coffee classified as a "strictly soft" beverage - Abreu, Celeste Maria Patto de; Carvalho, Vânia Déa de; Botrel, Neide (Pesquisa Agropecuaria Brasileira, 1996)
The purpose of the present work was to determine the effect of "green" defect addition levels on the chemical composition of coffee classified by cup proof in "strictly soft". It was determined the poliphenoloxidase and peroxidase activities, colour index, total acidity, phenolic compounds and crude protein values in coffee "strictly soft", containing the following levels of "green defect": 0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% and 100%. It was concluded that the increase in green defect addition decreased poliphenoloxidase and peroxidase activities as well as colour index; and increased total acidity and phenolic compounds contents but did not affect the crude protein contents.